From the Bay of Pigs to Lake Tanganyika : non-state armed actors in the Congo crisis, 1960-1967 - (:unkn) unknown (My University, 2018)
Whereas the Democratic Republic of the Congo became independent in June 1960 within a very short space of time the country will be torn apart by a series of secession and rebellions. In Katanga, secession is supported by the arrival of a mercenary army and the United Nations is sent to restore order by ridding the Congo of these foreign forces.The UN mission complete and its forces having been withdrawn by July 1963, the Congolese government will then be confronted by a popular rebellion in rural areas of the Congo. Supported by the People's Republic of China and radical African nations this communist-inspired rebellion makes rapid progress and soon two-thirds of the Congo is in the hands of the Simbas, the name adopted by the rebels. By August 1964 the Simbas have reached Stanleyville, the Congo's second largest city, and threaten to kill hundreds of mainly Belgian hostages. With the Congolese National Army being unfit to defeat the rebellion alone, it is reinforced by hundreds of white mercenaries. Seeing the rebellion and its communist support as a threat to its ideologies of Containment and the Domino Theory, the United States also provides military assistance in the shape of an air force and a small commando unit. Known collectively as the Makasi, these US covert forces comprise of Cuban Exiles recruited and paid by the CIA. Many of these Exiles took part in the Bay of Pigs invasion in April 1961. These Exiles join the list of CIA covert forces who have taken part in secret operations in China and in Guatemala. They will be joined by more veterans of the failed invasion in 1965 when a naval force is created to patrol Lake Tanganyika. It is from here that rebel forces are being supplied with food and weapons provided by communist-bloc nations and supporters. Moreover, from April 1965, the rebel forces will also be joined by Che Guevara who has hopes of starting up a popular revolution in the heart of Africa. Guevara's presence in the Congo being ra
Keywords: African Research